Repression of PUM1-mediated mRNA decay activates translesion synthesis after DNA damage - Toshimichi Yamada; Xiaoning Sun; Nobuyoshi Akimitsu (Molecular & Cellular Oncology, 2020)
Biological roles of Pumilio1 (PUM1) in ubiquitous cells remain unclear. Here we identify 48 degrading target mRNAs by combined analysis of transcriptome-wide mRNA stabilities and the binding of mRNAs. Further analysis revealed that cells respond to DNA damage by inhibiting PUM1-mediated mRNA decay to activate translesion synthesis (46/50).